2019
DOI: 10.1007/s13187-019-01646-8
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in BRCA1/2 and Multigene Panel Testing Among Young Breast Cancer Patients

Abstract: Genetic testing for hereditary breast and ovarian cancer (HBOC) is recommended for breast cancer patients diagnosed at age ≤ 50 years. Our objective was to examine racial/ethnic differences in genetic testing frequency and results among diverse breast cancer patients. A retrospective cohort study among women diagnosed with breast cancer at age ≤ 50 years from January 2007 to December 2017 at Columbia University in New York, NY. Among 1503 diverse young breast cancer patients, nearly half (46.2%) completed HBOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
3
20
1
Order By: Relevance
“…In the Jones et al study, 683 mixed ethnic women underwent genetic testing; African ethnic women had majority of gene mutation with pathogenic variant in BRCA1/2, CHEK2 and ATM [ 26 ]. Asians were the next population with gene mutations, followed by Hispanics and lastly Caucasian.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Jones et al study, 683 mixed ethnic women underwent genetic testing; African ethnic women had majority of gene mutation with pathogenic variant in BRCA1/2, CHEK2 and ATM [ 26 ]. Asians were the next population with gene mutations, followed by Hispanics and lastly Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…Asians were the next population with gene mutations, followed by Hispanics and lastly Caucasian. In the Asian population variant of uncertain significance was higher compared to other ethnic groups [ 26 ]. Despite these results African women were less likely to undergo genetic counseling compared to Caucasian women [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This slightly higher frequency in African Americans was not statistically significant but was similarly observed in a recent report by Jones et al . [ 13 ]. Though it is typically reported that closer to 20% of hereditary breast cancer cases have a high-risk, pathogenic variant in a clinically relevant gene [ 1 ], the percentage of cases in this study with such variants is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that early age of onset is a hallmark of hereditary breast cancer [ 1 ], genetic risk factors may be contributing to this disparity. Interestingly, African Americans have been reported to have more variants of uncertain significance (VUSs) in clinically valid breast/ovarian cancer genes [ 10 13 , 15 , 16 ], which warrant further investigation using NGS gene panels. Ultimately, a complete spectrum of breast cancer risk variants needs to be defined to provide greater insight towards African American breast cancer disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Germline genetic testing is increasingly carried out for patients with an elevated risk of hereditary diseases such as breast and ovarian cancer (Jones et al , 2019). These tests frequently yield previously-unseen and often extremely rare genetic variants, amongst which it can be difficult to identify the subsets of pathogenic and benign variants (Blazer et al , 2015).…”
Section: Introductionmentioning
confidence: 99%